1997
DOI: 10.1038/sj.ejcn.1600393
|View full text |Cite
|
Sign up to set email alerts
|

Zinc levels in maternal milk: the influence of nutritional status with respect to zinc during the third trimester of pregnancy

Abstract: Objective: To study the relationship between nutritional status with respect to zinc during the third trimester of pregnancy and levels of the same mineral in transition milk (days 13 and 14 of lactation) and mature milk (day 40 of lactation). Design: Longitudinal study. Subjects: A group of 57 healthy, lactating mothers aged between 18 and 35 y (27 AE 3.7) whose pregnancy and labour were attended by the Department of Obstetrics and Gynaecology of Cuenca INSALUD Hospital, Spain. Interventions: Zinc intake duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 33 publications
(39 reference statements)
2
14
0
Order By: Relevance
“…Although zinc intakes of women in our study were lower than the recommendation, mean values were comparable to those reported by other authors in different populations [22,23]. In addition to total amount of zinc, it is important to consider bioavailability; in Mexican diets the availability of zinc (measured as solubility) was poor [24].…”
Section: Food Components Of Mexican Lactating Womensupporting
confidence: 87%
“…Although zinc intakes of women in our study were lower than the recommendation, mean values were comparable to those reported by other authors in different populations [22,23]. In addition to total amount of zinc, it is important to consider bioavailability; in Mexican diets the availability of zinc (measured as solubility) was poor [24].…”
Section: Food Components Of Mexican Lactating Womensupporting
confidence: 87%
“…Supplementation with vitamin A would reduce morbidity and mortality. Such a combined iron-zinc-vitamin A supplementation would probably have to be started at 4-6 mo of age, or even earlier when mothers are malnourished (42,43). The results of our study suggest that supplementation would not need to be done daily but that a once-weekly supplement would be sufficient for reducing anemia and improving zinc and vitamin A status.…”
Section: Tablementioning
confidence: 70%
“…It is possible that the homeostatic adjustments during pregnancy reflect the mother’s zinc status prior to conception and that the lactation adjustments reflect zinc status during pregnancy. In a study of lactating Spanish women, maternal zinc intake during late pregnancy influenced mature milk zinc concentrations [83]. This continuum needs further study.…”
Section: Other Research Implicationsmentioning
confidence: 99%